VD_FINDINFO Jug / 2015 / 173 vom 14. August 2014 - VD Tribunal cantonal (2014)
IN DUBIO PRO REO, PRÉSOMPTION D'INNOCENCE, CONSTATATION DES FAITS, REFORMATIO IN PEJUS, RECOURS JOINT, CONFISCATIONDROIT PÉNAL | 69 al. 1 CP, 10 CPP (CH), 267 CPP (CH), 399 al. 4 CPP (CH), 401 CPP (CH)